New normals, from talk to gesture. Issue 2 (4th May 2021) - Ingraham, Chris
ABSTRACT: Despite all the news coverage and online chatter about the repercussions of COVID-19, the pandemic has underscored the material limitations of public discourse to redress a health crisis of such magnitude. No amount of talk or deliberation will cure a virus of this scale. If part of the work of cultural studies is to identify the ways a given conjuncture shapes and delimits the felt experience of everyday life, then one charge of our work now is to examine the emergence of those 'new normals' that the novel coronavirus has spawned. One of these emergent new configurations of the everyday has been the spread of concerned gestures as a counterpoint to the usual talk talk talk of communicative capitalism. Gestures of concern, from chalking sidewalks to applauding essential workers, build the affective commonwealths that cultivate solidarity in times of protracted precarity. Exceeding Raymond Williams's notion of 'structures of feeling, ' affective commonwealths are a resource built from ordinary people whose gestural rituals enact the sorts of worlds that talk alone just can't bring about. This essay makes a case for the importance of such gestures and suggests they deserve further attention in and beyond the context of the pandemic.